Advancing Zakat Performance through a Triple Helix Framework: An ANP-Based Prioritization of Solutions from South Sulawesi-Indonesia - Azwar Azwar; Abur Hamdi Usman; Hassan Shakeel Shah; Mutsalim Khareng; Lilly Suzana Shamsu (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2026)
As an essential component of Islamic social finance, zakat possesses considerable potential to reduce poverty and promote inclusive socio-economic development. However, the performance of zakat management remains suboptimal in many regions due to persistent governance challenges involving multiple stakeholders. This study aims to identify and prioritize strategic solutions for improving zakat performance in South Sulawesi, Indonesia, using the Analytic Network Process (ANP) within a Triple Helix governance framework. An exploratory sequential mixed-methods design was employed, in which qualitative findings were used to identify and validate governance determinants before being incorporated into the ANP model for priority analysis. The findings indicate that government-based solutions constitute the highest strategic priority, particularly strengthening regulatory certainty and policy support. Institutional reforms, including improvements in transparency, accountability, governance, and service quality, rank second, while community-based initiatives focusing on zakat literacy and public engagement serve as complementary priorities for sustainable zakat development. These results demonstrate that improving zakat performance requires coordinated and synergistic collaboration among government, zakat institutions, and society rather than isolated interventions by individual stakeholders. Methodologically, this study contributes by integrating the Triple Helix governance framework with the ANP approach to generate evidence-based strategic priorities for zakat governance. The proposed framework provides practical guidance for policymakers and zakat management organizations in designing integrated governance strategies to maximize the socio-economic impact of zakat.